Weed associated to emblematic crops in Yucatan state, Mexico - Avilés-Baeza, Wilson Ildelfonso; Ramírez-Jaramillo, Genovevo; Lozano Contreras, Dra. Mónica Guadalupe (Ecosistemas y Recursos Agropecuarios, 2025)
Weeds compete with crops for essential resources such as light, water, and nutrients, reducing their yield. The aim of the present study was to evaluate the abundance, dominance, and coverage of weed species present in three agricultural crops in two municipalities of the state of Yucatán. A total of 35 weed species belonging to 31 genera and 16 families were identified, with Fabaceae and Poaceae being the most represented. In henequen, the dominant species were Melanthera nivea (61.1%), Dactyloctenium aegyptium (46.6%), and Malvastrum corchorifolium (37.2%). In habanero pepper, Euphorbia hyssopifolia (61.8%) and Megathyrsus maximus (52.4%) were the most prevalent. Meanwhile, the sweet orange crop showed less diversity, with Cyperus rotundus and Sorghum halepense as the predominant species. The results suggest that weed dominance is influenced by the type of crop and the agricultural practices applied in each plot, with the latter playing a key role in their distribution.